Student factors, theoretical comprehension, professional support, and peer support as predictors of fourth-year nursing students' clinical competence - Soputri, Nilawati
The main purpose of this study was to investigate how student factors, theoretical comprehension, professional support from clinical instructors (CIs) and staff nurses (SNs), and peer support, correlated with the predicted the 4th-year nursing students’ clinical competence (NSCC). The study used the descriptive correlational survey design. Three hundred sixty-four participants were selected by stratified random sampling method. They responded to the Career Development Interest Inventory. Nursing Clinical Teacher Effectiveness Inventory, Staff Nurse Supportive Scales, Nursing Students’ Peer Supportive Scales, and demographic profiles. The 4th-year nursing students’ theoretical comprehension (NSTC) was measured by their theoretical grade, while NSCC was measured by the clinical grade of related learning experiences.